Conocimientos de bioseguridad durante el uso de la lámpara de fotocurado en odontología estética - Calero, Jenny; Castro, Gloria; Martínez, Monica (Revista Estomatología, 2004)
This study determined students´ knowledge about ocular lesions and protection associated to the use of the light curing lamp at University of Valle in Cali, Colombia. One hundred and one dentistry students evaluated by surveys and the statistical analysis was made with the software Epi-info. It was found that students accept to use methods of ocular protection but they do not know the rationale for its use, since they do not know the damages that the light emitted by the curing lamp may produce at ocular level. In addition, they do not know the type of light emitted by each one’s lamp used in their daily practices. These results will permit to clarify and to improve the students´ knowledge about the damages and the ocular protection in the use of the curing lamp, and thus to give them the recommendations for a better use of it and to assure them a suitable protection. Key Words: Light curing lamps. Dentistry student’s knowledge on eye protection devices. Biosecurity.